The protective mechanism of SIRT1 on cartilage through regulation of LEF-1 - Xueyu Hu (BMC Musculoskeletal Disorders, 2021)
Abstract Background Osteoarthritis (OA) is a chronic degenerative disease that suppresses middle-aged and older people worldwide. Silent information regulator 1(SIRT-1) is associated with several age-related diseases, such as cardiovascular diseases, neurodegenerative diseases and tumors, etc. The protective role of SIRT-1 in bone and joint diseases has become increasingly well known. Objective To explore the relationship between SIRT-1 and its related factors in OA. Methods Fresh tibial plateau specimens were collected from 30 patients with knee OA who underwent total knee arthroplasty. According to the results of Safranin O Fast Green Staining, hematoxylin–eosin staining and the OARSI grade developed by the International Association for the Study of Osteoarthropathy, the specimens were divided into the mild group, moderate group and severe group, and the damage of cartilage was evaluated. SIRT-1 protein levels in cartilage samples were analyzed by immunohistochemistry. Then, take 60 8-week-old female C57BL/6 J mice and apply the Destabilization of the medial meniscus (DMM) to induce OA. Mice were randomly divided into normal group (sham), model group (model), and post-modeling drug administration group (srt), and each group was further divided into 2 weeks after modeling (2 W) and 8 weeks after modeling (8 W) according to the time after surgery. The degenerative degree of a knee joint in mouse knee cartilage samples was evaluated using Safranin O Fast Green Staining and OARSI grade. Immunohistochemical techniques assessed the protein levels of SIRT-1, β-catenin, LEF-1, MMP-13 and Collagen II in cartilage samples. The protein levels of β-catenin, LEF-1 and MMP-13 in the samples were assessed by the immunohistofluorescence technique. The mRNA expression of SIRT-1 and LEF-1 in mouse cartilage samples was evaluated by real-time quantitative polymerase chain reaction (qPCR). Results In the human cartilage samples, according to the results of Safranin O Fast Green Staining, compared with the mild group, the moderate group and the severe group showed damage cartilage layer structure, the number of chondrocytes decreased, the cell hypertrophic, the cartilage surface discontinuous, and the OARSI grade increased. The severe group had severe cartilage injury and the highest OARSI grade. In the mice cartilage samples, according to immunohistochemical analysis, the protein levels of β-catenin, LEF-1 and MMP-13 in cartilage specimens of model 2 W and model 8 W groups were significantly increased than the sham 2 W and sham 8 W groups. The protein levels of SIRT-1 and Collagen II were significantly decreased (P < 0.05), the results of srt 2 W and srt 8 W groups were between the sham group and the model group. According to immunofluorescence analysis, the protein levels of β-catenin, LEF-1 and MMP-13 in model 2 W and model 8 W groups were significantly increased than sham 2 W and sham 8 W groups. The results of srt 2w and srt 8w groups were between the sham group and the model group. According to the real-time qPCR results: Compared with sham 2 W and sham 8 W groups, the mRNA expression of SIRT-1 in model 2 W and model 8 W groups was significantly decreased, while the mRNA expression of LEF-1 was significantly increased. In contrast, the results of srt 2 W and srt 8 W groups were between the sham group and the model group. Conclusion SRT-1720, as a specific activator of SIRT-1, does increase the protein level of SIRT-1. SIRT-1 may play a protective role in cartilage by regulating the expression of LEF-1 and related inflammatory factors in OA.